PENGEMBANGAN DAN PENGAPLIKASIAN MEDIA VIDEO VISUAL DALAM PENINGKATAN PENGETAHUAN GIZI SEIMBANG PADA REMAJA - Firmansyah Firmansyah; Lutfi Nur Ratna Kusuma; Siti Zulaekah; Luluk Ria Rakhma (Poltekkes Kemenkes Pontianak, 2022)
Nutrition problems that are often found in adolescents include nutritional imbalances, so they need knowledge about balanced nutrition. To increase knowledge of balanced nutrition, a tool is needed in the form of audio-visual media. This audio-visual media is considered effective in increasing knowledge. This study aimed to develop and apply audio-visual media to increase knowledge of balanced nutrition in adolescents. This study used the Research and Development (RnD) method with the analysis, planning, development, and implementation stages. In this study, the research subjects were material and media experts, and the target and object of this research were audio-visual media. Based on the media validation test, the assessments of the validators of material experts, media experts, and targets, audio-visual was included in the appropriate category with an average value of 4.3, while for CVI calculations a score of 1 means that each material expert agrees that the material in the audio-visual was relevant. The results of the application of audio-visual media obtained an average value of 6.7 pretests and 9.7 posttests so there was an increase in knowledge of 44.7%. Audio-visual media was appropriate to be used as a means of information to increase knowledge of balanced nutrition in adolescents. So that nutrition education methods with related media can be developed and applied.